Combined trauma in peaceful time. - V. A. Chaika (Medičnì Perspektivi, 2014)
In the article epidemiological features of combined trauma (CT), characteristic for the industrial region were summarized. 486 cases of CT were analyzed for the period from 2010 to 2012. Male patients dominated. 267 (54.9%) patients were the age from 25 to 44 years. Most often the damage occurred in 2 anatomic regions (AR) - 224 (46.1%), 3 AR - 177 (36.4%) and 4 or more - 85 (17.5%). Traumatic brain injury - 94.2%, skeletal trauma - 70.6%, the trauma of the chest and abdomen - 68.4% and 35.7%, respectively prevailed. Injury of the abdominal cavity as a dominant one - 148 (30.5%) occupied the first place. In 17 (3.5%) cases it was impossible to establish the dominant damage. Mortality rate was directly dependent on the type of the trauma and patient's age. Maximum values were found in the combined brain injury and that of abdominal organs - 28.6%, as well as in the group of patients older than 60 years - 35.1%. From 2010 to 2012 the overall mortality decreased by 3.5%.